2008
DOI: 10.1021/jp806806j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Long-Range Electron Transport in Molecular Junctions

Abstract: A study of long-range electron transport through a series of molecular junctions comprised of π-conjugated molecules is presented. A theoretical model is built by using a quantum chemistry based Landauer theory combined with Green's function formalism and the D'Amato-Pastawski model to describe the electronic conduction in the presence of incoherent scattering effects. Effects of incoherent transport on the total conductance under the nonbiased, stationary, and nondissipative conditions are investigated. Calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 72 publications
0
47
0
Order By: Relevance
“…More recently, it was applied to investigate e.g. electronic conduction in organic and biological molecular junctions [32][33][34][35][36][37] . Particularly, it was recently demonstrated in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was applied to investigate e.g. electronic conduction in organic and biological molecular junctions [32][33][34][35][36][37] . Particularly, it was recently demonstrated in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, incoherent elastic and inelastic scattering effects are included in a phenomenological manner, by augmenting the noninteracting electronic Hamiltonian with probe terminals through which electrons lose their phase memory and (possibly) exchange energy with environmental degrees of freedom 48,49 . While the technique was originally introduced to study decoherence effects in mesoscopic devices, it was recently applied to explore electronic conduction in organic and biological molecular junctions [50][51][52][53] , as well as anharmonic effects in (purely) phononic quantum conduction [54][55][56] . Particularly, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with the LBP technique had demonstrated its utility as a means to phenomenologically describe low-bias incoherent effects in mesoscopic conductors 25,[28][29][30][31][32][33][34][35][36] and molecular junctions 27,[37][38][39][40][41][42] These simulations indicate that the LBP technique can reproduce several key features in molecular electronic conduction: A "Kramers-like" turnover of conductance as a function of the so-called dephasing strength, an onset of a thermally activated conductance at high temperature, and a transition from tunneling to ohmic conduction when increasing the molecular size 27 . It was also shown in Ref.…”
Section: Introductionmentioning
confidence: 99%